Assessing the potential outcomes of achieving the World Health Organization global non-communicable diseases targets for risk factors by 2025: is there also an economic dividend?. (April 2019) - Devaux, M.; Lerouge, A.; Ventelou, B.; Goryakin, Y.; Feigl, A.; Vuik, S.; Cecchini, M.
Abstract: Objectives: This study assesses the change in premature mortality and in morbidity under the scenario of meeting the World Health Organization (WHO) global targets for non-communicable disease (NCD) risk factors (RFs) by 2025 in France. It also estimates medical expenditure savings because of the reduction of NCD burden. Study design: A microsimulation model is used to predict the future health and economic outcomes in France. Methods: A 'RF targets' scenario, assuming the achievement of the six targets on RFs by 2025, is compared to a counterfactual scenario with respect to disability-adjusted life years and healthcare costs differences. Results: The achievement of the RFs targets by 2025 would save about 25, 300 (and 75, 500) life years in good health in the population aged 25–64 (respectively 65+) years on average every year and would help to reduce healthcare costs by about €660 million on average per year, which represents 0.35% of the current annual healthcare spending in France. Such a reduction in RFs (net of the natural decreasing trend in mortality) would contribute to achieving about half of the 2030 NCD premature mortality target in France. Conclusions: The achievement of the RF targets would lead France to save life years and life years in good health in both working-age and retired people and would modestly reduce healthcare expenditures. To achieve RFs targets and to curb the growing burden of NCDs, France has to strengthen existing and implement new policy interventions. Highlights: We model risk factors (RFs) reduction by 2025 and assess impact by 2030 in France. Reducing RFs would contribute to half of the premature mortality SDG target. Reducing RFs would improve healthy life years. Reducing RFs would reduce healthcare costs by about €660 million yearly.